The impact of exchange rate changes and monetary policy on stock prices in financial markets: an analytical study of China for the period (2003 - 2014) - Hashem Jabbar Al-Husseini,; Ayat Hussein Ali, (Iraqi Journal for Administrative Sciences, 2024)
We had to search the financial markets of China and represents the goal of research is to diagnose the main mouthpiece of the financial market performance indicators, and to identify the relevant variables, the performance of financial markets, as well as detect effects that variables of b (the exchange rate, interest rate, money supply) as independent variables in the most important financial market performance indicators for China and is the (market value of shares traded, shares traded turnover, Shanghai index and Shenzhen index) during the period (2003-2014). And its impact on stock prices in the financial markets in China. Came study shows everything related to the variables of the market value of shares traded, shares traded turnover, Shanghai index and Shenzhen index) and its impact on stock prices in the financial markets in China. . As through the standard analysis note that more variables impact on stock prices in the financial markets of China are the foreign exchange rate and money supply, where their influence appears on the market value of traded and traded turnover of shares, the more factors that affect the index SHANGHAI and index SHENZHEN two foreign exchange rate and interest rate.